Analysis of indices of reliability of cascade thermoelectric coolers in various current modes - Zaikov, Vladimir; Mescheryakov, Vladimir; Zhuravlov, Yurii (Eastern-European Journal of Enterprise Technologies, 2016)
Strict requirements for the operating conditions for thermally loaded elements of radio-electronic systems contribute to essential relevance of the problem of increasing the indices of reliability of thermoelectric coolers in the implementation of their thermal modes. This leads to the need for increasing the indices of reliability not only through the use of new materials, design and technological solutions, but also optimization of the current modes of thermoelectric modules. The aim of this work is the search for the possibility of increasing the indices of reliability of cascade thermoelectric coolers, without changing their design parameters and material of thermoelements, by the selection of current modes at varied operating conditions. In the work we proposed a mathematical model of interrelation of the relative magnitude of the failure rate of two-stage thermoelectric device with the number of thermoelements, relative operating current, thermal load, and temperature difference in the temperature range of workability of a cooler. We carried out comparative analysis of the main significant parameters and indices of reliability of two-stage thermoelectric coolers for different current modes of operation in a wide range of temperature differences from =60 K to =90 K, taking into account the thermal load. It was demonstrated that with an increase in the general temperature difference, the ratio of the number of thermoelements in the adjacent cascades increases, the total number of thermoelements increases, the refrigeratory coefficient decreases, the relative magnitude of the failure rate grows and the probability of failure-free operation decreases. We obtained expression for determining the optimum relative operating current, at which the minimum value of relative number of thermoelements in the cascades is observed. Comparative analysis of the main parameters and indices of reliability demonstrated the possibility of selection and implementation of different current modes of operation of a cascade thermoelectric cooler for the varied operation conditions. Two extreme (characteristic) modes were proposed: the mode providing a minimum number of thermoelements, that is, minimum mass and overall dimensions of device; and the mode, providing the minimum failure rate and the maximum probability of failure-free operation. The proposed modes may be applied in the process of designing thermoelectric devices of minimum mass and increased reliability.